Determinants of msme performance: financial inclusion, financial literacy, and financial management capability in karang berombak subdistrict - Winda Simanjuntak; Endang B. Sinaga; Putra Raja Tunggal Hasugian (Institute of Computer Science (IOCS), 2026)
This study examined the determinants of micro, small, and medium-sized enterprise performance, focusing on financial inclusion, financial literacy, and financial management capability in Karang Berombak Subdistrict. The research problem addressed the extent to which these financial factors contributed to improving enterprise performance. A quantitative research approach was applied, and data were collected through structured questionnaires distributed to micro, small, and medium-sized enterprise owners. The sample consisted of 86 respondents. Descriptive statistical analysis and multiple linear regression analysis were used to examine the relationships between financial inclusion, financial literacy, financial management capability, and enterprise performance. The findings showed that financial inclusion had a significant effect on micro, small, and medium-sized enterprise performance, indicating that access to financial services supported business growth and operational effectiveness. Financial literacy also had a significant effect on enterprise performance, suggesting that financial knowledge played an important role in business decision-making. However, financial management capability did not have a significant effect on enterprise performance. These results implied that while access to financial services and financial knowledge were critical determinants of enterprise performance, financial management capability alone was not sufficient to improve performance. The study concluded that strengthening financial inclusion and financial literacy was essential to enhance micro, small, and medium-sized enterprise performance in Karang Berombak Subdistrict